2016
DOI: 10.1007/s40519-016-0313-5
|View full text |Cite
|
Sign up to set email alerts
|

Medical comorbidity of binge eating disorder

Abstract: BED is associated with substantial medical comorbidity beyond obesity. Further study of the general medical comorbidity of BED and its relationship to obesity and co-occurring psychiatric disorders is greatly needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
59
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(73 citation statements)
references
References 88 publications
1
59
0
2
Order By: Relevance
“…Survey (Kessler et al, 2013) and with medical findings highlighted in a recent review (Olguin et al, 2016) which concluded that type-2 Notes. All analyses adjusted for complex survey design of NESARC-III.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Survey (Kessler et al, 2013) and with medical findings highlighted in a recent review (Olguin et al, 2016) which concluded that type-2 Notes. All analyses adjusted for complex survey design of NESARC-III.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Olguin et al (2016) suggested that more studies are needed to determine whether the associations between BED and these somatic conditions are above and beyond the effects of obesity or other psychiatric comorbidity. In addition, Olguin et al (2016) suggested that more studies are needed to determine whether the associations between BED and these somatic conditions are above and beyond the effects of obesity or other psychiatric comorbidity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…So-called “food addiction” has been hypothesized to underlie many cases of obesity and eating disorders, which may collectively comprise the most prevalent and deadliest form of addictive behavior (Agh et al, 2016; Fichter & Quadflieg, 2016; Flegal, Kit, Orpana, & Graubard, 2013; Flegal, Kruszon-Moran, Carroll, Fryar, & Ogden, 2016; Hoang, Goldacre, & James, 2014; Kroes, Osei-Assibey, Baker-Searle, & Huang, 2016; Micali et al, 2017; Mitchell, 2016; Olguin et al, 2017; Perez, Ohrt, & Hoek, 2016; Smink, van Hoeken, & Hoek, 2013; Westmoreland, Krantz, & Mehler, 2016). In the United States, ~3 of 4 men and 2 of 3 women were overweight (25<body mass index [BMI]<30) or obese (BMI>30) in 2013–2014, and ~33% of overweight/obese people (and ~54% of patients undergoing bariatric surgery for obesity) met diagnostic criteria of the Yale Food Addiction Scale (Flegal et al, 2016; Long, Blundell, & Finlayson, 2015; Pursey, Stanwell, Gearhardt, Collins, & Burrows, 2014).…”
Section: Compulsive Eatingmentioning
confidence: 99%
“…Anorexia nervosa and bulimia nervosa pose a heightened risk for suicide (Franko & Keel, 2006) and are linked with osteoporosis, gastrointestinal, cardiovascular, and endocrine system pathologies (Crow, 2005; Klein & Walsh, 2003; Mehler & Krantz, 2003). Binge eating disorder is associated with psychiatric comorbidity and severe obesity (Haines & Neumark-Sztainer, 2006; Hudson, Hiripi, Pope, & Kessler, 2007; Wade, Bergin, Tiggemann, Bulik, & Fairburn, 2006) in addition to medical conditions such as type 2 diabetes, metabolic syndrome, sleep disorders, asthma, menstrual and gastrointestinal issues, and cardiovascular disease that are not accounted solely by weight gain (Mitchell et al, 2015; Olguin, Fuentes, Gabler, Guerdjikova, Keck & McElroy, 2017). Given the negative consequences of eating disorders, it is vital to understand the prevalence of eating disorders and risk factors for all ethnic groups.…”
mentioning
confidence: 99%